2010
DOI: 10.1093/molehr/gaq079
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of recurrent pregnancy loss: impaired natural embryo selection

Abstract: Recurrent pregnancy loss (RPL) is a common and distressing disorder. Chromosomal errors in the embryo are the single most common cause, whereas uterine factors are invariably invoked to explain non-chromosomal miscarriages. These uterine factors are, however, poorly defined. The ability of a conceptus to implant in the endometrium is normally restricted to a few days in the menstrual cycle. A limited 'window of implantation' ensures coordinated embryonic and endometrial development, thereby minimizing the risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
116
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(126 citation statements)
references
References 99 publications
5
116
0
5
Order By: Relevance
“…Nieprawidłowa reakcja doczesnowa stwarza możliwość późnej implantacji, zagnieżdżenia nieprawidłowych zarodków oraz późniejszych problemów z wytworzeniem zaczątków łożyska i jego dalszym funkcjonowaniem. "Dialog receptorowy" pomiędzy endometrium a zarodkiem jest możliwy dzięki obecności wielu fizjologicznych czynników, również tych o charakterze immunologicznym, takich jak przykładowo liczne cytokiny [3][4][5][6][7]. U kobiet charakteryzujących się prawidłową płodnością szacuje się, iż około 30% zarodków ulega utracie jeszcze przed implantacją, a kolejne 30% po implantacji, ale jeszcze przed mającą wystąpić menstruacją.…”
Section: Opis Stanu Wiedzyunclassified
See 2 more Smart Citations
“…Nieprawidłowa reakcja doczesnowa stwarza możliwość późnej implantacji, zagnieżdżenia nieprawidłowych zarodków oraz późniejszych problemów z wytworzeniem zaczątków łożyska i jego dalszym funkcjonowaniem. "Dialog receptorowy" pomiędzy endometrium a zarodkiem jest możliwy dzięki obecności wielu fizjologicznych czynników, również tych o charakterze immunologicznym, takich jak przykładowo liczne cytokiny [3][4][5][6][7]. U kobiet charakteryzujących się prawidłową płodnością szacuje się, iż około 30% zarodków ulega utracie jeszcze przed implantacją, a kolejne 30% po implantacji, ale jeszcze przed mającą wystąpić menstruacją.…”
Section: Opis Stanu Wiedzyunclassified
“…Oznacza to, iż kobiety z nieprawidłową funkcją endometrium mogą pozornie wydawać się bardzo płodne, jednak w rzeczywistości dochodzi u nich do opóźnionej, w stosunku do zdrowych kobiet, eliminacji nieprawidłowych zarodków, kiedy to ciąża jest już klinicznie stwierdzona. Czas osiągania kolejnej ciąży jest przez te kobiety wprawdzie krótki, ale liczba późniejszych poronień wysoka [4,8].…”
Section: Opis Stanu Wiedzyunclassified
See 1 more Smart Citation
“…Ces différences reflètent probablement les procédés expérimentaux variés ; de fait, aucun marqueur fiable de la réceptivité maternelle ne s'est imposé jusqu'à aujourd'hui [42]. Cependant, le concept d'endomètre biosenseur de l'implantation embryonnaire émerge [43]. De récentes publications démontrent l'existence d'une interaction étroite entre l'IL1 et l'hCG, deux signaux embryonnaires précoces qui sont capables de moduler le phénotype des cellules de l'endomètre.…”
Section: Dernières Avancéesunclassified
“…It is thought that decidualization determines the length of the implantation window 2 . We have shown that there is significant variation in the Correspondence length of the implantation window 3 , and it has been hypothesized that a prolonged window is associated with an increased risk of miscarriage and obstetric disorders caused by placental dysfunction, such as pre-eclampsia and intrauterine growth restriction 4,5 . It is therefore plausible that the presence of a CS scar may impact on decidualization and have an effect on placentation.…”
Section: Replymentioning
confidence: 99%